Perubahan Iklim Kala Pliosen – Plistosen Daerah Bumiayu Ditinjau Dari Bukti Palinologi - Setijadi, Rachmad (Dinamika Rekayasa, 2008)
The objective of the research was describing Pliocene-Pleistocene climatic changes in Bumiayu area based on palynology evidence. The applied method in this research was survey. For sediment sampling used surface sampling method. There are two phases in this research which are field and laboratory research. Thirty six analyzed samples took from Kalibiuk and Kaliglagah Formation in Cisaat river, Bumiayu. The relative age in Bumiayu area on Kalibiuk and Kaliglagah Formation is Late Pliocene-Pleistocene mark on last appearance Stenochlaenidites papuanus and followed by eight times climatic changes, which caused the changes of the flora and vegetation.